QUANTUM LEARNING PAI: INTEGRASI MODERNITAS PSIKOLOGI DAN TRADISI TARBIYAH - M. Rizal Umam; Ansori; Miftahussurur, Wildan (LPPM STAI Muhammadiyah Probolinggo, 2025)
The need for innovative learning models in Islamic Religious Education (PAI) has become urgent to address contemporary challenges while preserving spiritual authenticity. This study explores the integration of Quantum Learning in PAI, which combines modern psychological principles with traditional tarbiyah values. A qualitative library research approach was employed, analyzing literature on Quantum Learning, educational psychology, and Islamic educational concepts. Data were processed through reduction, categorization, and descriptive-analytical interpretation. The results indicate that Quantum Learning significantly enhances student motivation, supports the internalization of religious values, and strengthens character development. Techniques such as the TANDUR model, mind mapping, and creative learning strategies can be harmonized with tarbiyah principles, including sincerity, adab (proper manners), and worship-oriented goals. Consequently, PAI instruction shifts from rote knowledge transfer to fostering cognitive, affective, and spiritual competencies. This integration offers a strategic solution to meet 21st-century educational demands without compromising Islamic teachings. Teacher training and adequate learning resources are essential to optimize its implementation.